Axial compressive behavior of laminated bamboo lumber columns with a chamfered section. (October 2021) - Hong, Chaokun; Li, Haitao; Xiong, Zhenhua; Lorenzo, Rodolfo; Li, Xin; Wang, Zhen
Abstract: The axial compressive behavior of laminated bamboo lumber (LBL) columns with a chamfered section was investigated using 15 specimens with lengths varying from 600 mm to 3000 mm; all considered samples had same square cross section of 100 mm × 100 mm with 10 mm chamfers at each corner. Axial compression tests were carried out to analyze the impact of slenderness ratios on failure modes, strain and ultimate bearing capacity of LBL columns. Two failure modes were observed i.e. compression failure and buckling failure. Obtained results on the ultimate vertical strain and ultimate load showed a downward trend with the increase in slenderness ratios; the correlation between the ultimate strain, ultimate load and the slenderness ratios were fitted. The approximate solution method was adopted to reveal the lateral deflections of buckling columns by a quartic functional model. Based on the ideal elastic–plastic constitutive model and Hill failure criterion, FEM was carried out to simulate the axial compression tests. The simulation results agreed well with both test and theoretical results, which verified the feasibility of proposed methods used under similar working conditions in this paper.